Dampak Implementasi PSAK No 69 terhadap Kinerja Pasar melalui Kinerja Perusahaan Sebagai Variabel Pemediasi Pada Perusahaan Sektor Agrikultur di Indonesia - Widya Fatmawati; Liza Alvia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze and evaluate the impact of the implementation of PSAK No. 69 (Biological Assets) on market performance, with company performance acting as a mediating variable, in agricultural sector companies listed in Indonesia. PSAK No. 69 was adopted to improve transparency and reliability in the financial reporting of biological assets, which are a significant component in the agricultural industry. The research adopts a quantitative approach, utilizing secondary data derived from the annual financial reports of companies and stock price information accessed via the Indonesia Stock Exchange (IDX) and the official websites of relevant companies for the period of 2018–2023.The study investigates the relationship between the intensity of biological assets and company performance, as measured by Return on Equity (ROE), as well as the relationship between company performance and market performance, as measured by Stock Return. The analysis results indicate that the intensity of biological assets has a significant positive impact on ROE. However, the direct effect of biological asset intensity on Stock Return is not statistically significant. Nevertheless, the mediation test reveals that ROE has a significant positive effect on Stock Return, thereby confirming the mediating role of ROE in the relationship between biological asset intensity and Stock Return.These findings imply that the implementation of PSAK No. 69 indirectly affects market performance through its influence on company performance. This highlights the importance of financial performance as a transmission channel in understanding the market implications of accounting regulation changes. The study provides useful insights for investors, regulators, and other stakeholders in evaluating the financial and market consequences of biological asset accounting standards in the agricultural sector.